School Literacy in Application-Based Learning Practices - Syaiful Marwan; Ratmiati Ratmiati; Wilda Fathia; Muspardi Muspardi; Ilhami Desrina; firman firman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The limited use of digital technology in the learning process poses a challenge to strengthening the literacy culture in elementary schools. This situation stems from teachers' limited competence in utilizing innovative and interactive learning applications. This community service initiative aims to enhance teachers' competence in using digital-based learning applications to strengthen school literacy practices. The project employed the Participatory Action Research (PAR) method, comprising stages of needs identification, planning, training implementation, mentoring, monitoring, and evaluation. Participants included elementary school teachers who received training on using Wordwall, Gamma, Prezi, and DeepSeek applications for instructional purposes and the development of teaching materials. The results indicate that the training and mentoring successfully improved the teachers' knowledge, skills, and confidence in integrating digital technology into the learning process. Most teachers successfully implemented at least one learning application in their classrooms—specifically Wordwall for assessment, Gamma and Prezi for material presentation, and DeepSeek as a reference for developing teaching materials. The implementation of these digital applications also positively impacted student interaction and learning motivation by fostering a more interactive, engaging, and meaningful learning experience. Thus, this community service program has proven effective in supporting the strengthening of school literacy culture while driving the transformation toward innovative learning suited to the demands of the digital era